Effect of Different Extraction Methods and Geographical Origins on the Total Phenolic Yield, Composition, and Antimicrobial Activity of Sugarcane Bagasse Extracts - Velázquez-Martínez, Victor; Valles-Rosales, Delia; Rodríguez-Uribe, Laura; Laguna-Camacho, Juan Rodrigo; López-Calderón, Hector Daniel; Delgado, Efren (Frontiers in Nutrition, 2022)
Several parameters, including particle size, solvent, temperature, and extraction method, affect phenolic compounds' extraction yield from a plant matrix. Considering the wide availability of sugarcane bagasse (SCB), this study analyzed the effect of different extraction methods and geographical origins on the yield, quality, and antimicrobial activity of phenolic compounds from SCB extracts. Samples from three geographical locations (Veracruz, Mexico; Santa Rosa, Texas, USA; and St. Mary, Louisiana, USA) were analyzed. Extraction was performed using an orbital shaker or ultrasonic bath at various times at a fixed temperature of 50°C, with 90% ethanol or methanol. The highest yield (5.91 mg GAE) was obtained using an orbital shaker for 24 h with 90% methanol as the solvent. HPLC-MS identified desferrioxamine b, baicalein, madecassic acid, and podototarin at different concentrations in all three SCB samples. The antimicrobial activity of these compounds was tested against Escherichia coli K12, Bacillus cereus, Enterobacter aerogenes, Streptococcus aureus, and Enterobacter cloacae. The antimicrobial activity was also tested against modifications of the Saccharomyces cerevisiae: the MutL Homolog 1 (MLH1), Slow Growth Suppressor (SGS1), O-6-MethylGuanine-DNA methyltransferase (MGT1), and RADiation sensitive (RAD14), carrying mutations related to different cancer types. In addition, the results were compared with the effect of ampicillin and kanamycin. The SCB extracts showed up to 90% growth inhibition against B. cereus at 200–800 μg/mL and 50% growth inhibition against S. aureus at 800 μg/mL. The inhibitory effect against modified yeast SGS1, RAD14, and MLH1 was 50–80% at 800 μg/mL. The percentage of inhibition and the phenolic compound contents differed depending on the origin of the SCB sample. These findings are promising for using this industrial byproduct to obtain compounds for nutraceutical, food additive, or medical uses.